Adaptation of the enterprise to the digital environment in the context of financial and economic security - Hurieieva, K. A. (ХНУРЕ, 2024)
The article defined the concept of financial and economic security of the enterprise. The list of information systems and technologies to ensure information and, in particular, financial and economic security of the enterprise is classified. The impact of digitalization on all aspects of enterprise security is analyzed
Keywords: financial security; economic security